Fostering Quality Education (SDG 4): Transforming QR Codes from 'Scanning' to 'Scaffolding' to Enhance Pre-Service Teachers' Critical Thinking - Ibrahim Ibrahim; Nurwahidah Nurwahidah; Ni Made Yeni Suranti; Nurkhaerat Alimuddin; Bahtiar Bahtiar; Maimun Maimun; Rangga Alif Faresta; Ismit Hi Karim; Trisno Setiawan (AMPLITUDO : Journal of Science and Technology Innovation, 2026)
This study addresses the "pedagogical digital gap" by proposing a shift from using technology for content delivery ("scanning") to cognitive support ("scaffolding"). It investigates the effectiveness of a QR-Code Integrated Inquiry model on pre-service primary teachers' critical thinking skills. Employing a quasi-experimental design with 60 participants, data were analyzed using ANCOVA. Findings revealed a highly significant difference () between groups. The experimental group achieved a notably higher adjusted mean (57.43) compared to the control group (34.88), with a massive effect size (). The intervention successfully reduced extraneous cognitive load, facilitating deep reasoning consistently across genders and science topics. The study concludes that re-engineering simple technology as scaffolding creates a robust, inclusive learning ecosystem for teacher education